PENGARUH PENGGUNAAN APLIKASI KECERDASAN BUATAN CHATGPT TERHADAP MINAT BELAJAR MATA PELAJARAN PPKn PADA PESERTA DIDIK DI SMP NEGERI 1 BOYOLANGU - Tegar Lutfian Budi; M. Abdul Roziq Asrori; Nurna Listya Purnamasari (CV. Adiba Aisha Amira, 2025)
This research aims to determine the influence of using the artificial intelligence application ChatGPT on students' interest in learning Civics (PPKn) at SMP Negeri 1 Boyolangu. The background of the study is the increasing integration of digital technology in education, where students often use AI-based tools to support their learning process. ChatGPT, as a text-based assistant, offers instant responses. However, unmoderated usage may negatively affect students' learning motivation and interest. This study employs a quantitative approach using questionnaires and statistical analysis through simple linear regression. The result shows a significance value of 0.000 with a t-count of 4.784 > t-table of 1.992, indicating a significant influence of ChatGPT usage on learning interest. Educators are encouraged to guide students in utilizing ChatGPT effectively as a supplementary tool rather than a substitute in the learning process.